Dynamic modeling of forest fires in the Eastern Hills of Bogota, Colombia - Ocampo-Zuleta, Korina; Beltrán-Vargas, Julio (Instituto de Ecología, A.C., 2018)
A simulation model is proposed to explain the dynamics of forest fires in the Eastern Hills of Bogotá, taking into account the number of fire events in the area, climatic variability and some factors such as hydric balance, vegetation cover, both  goods and ecosystem services, gorse (Ulex europaeus) and fire causes, which explain the incidence of each one in the generation of fires. This modeling was based on the correlation of the variables and obtaining  the formula of the model by linear regression. The behavior of the hydrological cycle takes into account two calendar years, one with low and another with greater precipitation, 2001 and 2011 respectively, where the importance of infiltration in the occurrence of forest fires and the dispersion of gorse is evident. Regarding the vegetation cover, the influence of the change of use in the soil is shown, in addition to being one of the causes in the loss of the goods and services provided by the forests, along with the rapid propagation of the invasive species, known as gorse that, due to its scattering and dry coverage as well as production abilities, it is clearly a factor in the spread of forest fires. Finally, it was determined that the number of forest fires is six (6) when the following conditions are given: first the temperature is high, secondly the precipitation is low and thirdly the fuel (vegetation) is kept constant.